hp-adaptive two-grid discontinuous Galerkin finite element methods for quasi-Newtonian fluid flows - Congreve, Scott; Houston, Paul; Wihler, Thomas P. (2013)
We develop the a posteriori error analysis, with respect to a mesh-dependent energy norm, of two-grid hp-version discontinuous Galerkin finite element methods for quasi-Newtonian flows. The performance of the proposed estimators within an hp-adaptive refinement procedure is studied through a numerical experiment.